Development of European apple canker on different cultivars in relation to planting time at three sites in the UK - Xu, Xiangming; Passey, Tom; Robinson-Boyer, Louisa; Mclean, Hamish; Saville, Robert; Papp-Rupar, Matevz (Frontiers in Horticulture, 2022)
European apple canker, caused by Neonectria ditissima, is a damaging disease of apple in many production regions worldwide. The pathogen infects apple trees through artificial or natural wounds. The most damaging phase of the disease is that cankers on main stems post-planting, most likely originating from infection in nurseries, can result in tree death in young orchards. Apple cultivars differ in their responses to the pathogen, which may be additionally affected by specific site factors. An experiment was conducted to study i) the susceptibility of seven cultivars to N. ditissima at three sites and ii) the effects of cold storage duration prior to planting on subsequent development of both main stem and peripheral cankers. Planting date had significant (albeit minimal effects) on the development of peripheral cankers only. Canker development differed greatly among the three sites and between the tested cultivars, with ‘Grenadier’ and ‘Golden Delicious’ being most resistant at all sites. The relative performance of cultivars in terms of canker development was generally consistent across the three sites. Nevertheless, the interaction between cultivar and site was still statistically significant for the development of main stem cankers, indicating that some site-specific factors may interact with cultivars to affect development of latent infections. Given the close proximity of the three sites (similar climatic conditions), the results indicate that further research is needed to investigate the effects of soil characteristics on canker development post-planting.